1975
DOI: 10.1063/1.321340
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen−implanted silicon. II. Electrical properties

Abstract: This paper presents measurements of capacitance−voltage, Hall−effect, and diode characteristics on nitrogen−implanted silicon as a function of anneal temperature. The results of these three types of electrical measurements are consistent and show that less than 1% of the implanted nitrogen exhibits donor effects following anneals in the temperature range ∼700−900 °C. Hall−effect measurements performed as a function of temperature indicate that nitrogen in silicon has an ionization energy of 0.017±0.002 eV. Roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…The behaviour of nitrogen complexes in silicon is quite involved with many nitrogen-interstitial and vacancy complexes predicted to be deep donors and acceptors. 42 Experimentally, however, nitrogen is known to transition from being a donor in Si with <1% activation at low annealing temperatures to being electrically inactive for annealing temperatures >850°C, 43 which should be the case for MOCVD grown AlN films (1050°C in our case, for instance). However, the simultaneous presence of high concentrations of oxygen and nitrogen atoms in the top surface of silicon indicates the possibility of forming Si-O-N complexes which can act as thermal acceptors.…”
Section: The Physical Origin Of Increased Surface Acceptor Concentrationmentioning
confidence: 85%
“…The behaviour of nitrogen complexes in silicon is quite involved with many nitrogen-interstitial and vacancy complexes predicted to be deep donors and acceptors. 42 Experimentally, however, nitrogen is known to transition from being a donor in Si with <1% activation at low annealing temperatures to being electrically inactive for annealing temperatures >850°C, 43 which should be the case for MOCVD grown AlN films (1050°C in our case, for instance). However, the simultaneous presence of high concentrations of oxygen and nitrogen atoms in the top surface of silicon indicates the possibility of forming Si-O-N complexes which can act as thermal acceptors.…”
Section: The Physical Origin Of Increased Surface Acceptor Concentrationmentioning
confidence: 85%
“…Early experiments suggested that N s possesses a shallow level (E c Ϫ0.017 eV). 43 However, this was later shown to be in error since the SL5 EPR center is associated with a ''deep level.'' 34 N-related levels at E c Ϫ0.19 eV (E 2 ) and E c Ϫ0.28 eV (E 3 ) have been observed in deep-level transient spectroscopy ͑DLTS͒ of n-type material doped during growth, 44 although these centers constitute, respectively, only 0.1% and 0.01% of the total nitrogen concentration of the material (10 15 cm Ϫ3 ).…”
Section: Introductionmentioning
confidence: 98%
“…9 On the other hand, when impurity-like concentrations are introduced into a semiconductor, the properties of nitrogen are determined by its interaction with the semiconductor host material. While, for instance, nitrogen doping of group IV semiconductors, such as diamond and silicon, introduces deep and shallow donors, [10][11][12] in conventional group III-V semiconductors nitrogen acts as an acceptor. 13 For ZnO, which is a promising material for blue and ultraviolet (UV) light-emitting diodes and lasers, use of nitrogen has been suggested to achieve p-type doping.…”
Section: Introductionmentioning
confidence: 99%